Spatially modulated and supersymmetric deformations of ABJM theory - Arav,I; Gauntlett,JP; Roberts,M; Rosen,C (Journal of High Energy Physics, 2019)
We construct supersymmetric solutions of $D=11$ supergravity, preserving 1/4of the supersymmetry, that are holographically dual to ABJM theory which hasbeen deformed by spatially varying mass terms depending on one of the twospatial directions. We show that the BPS equations reduce to the Helmholtzequation on the complex plane leading to rich classes of new solutions. Inparticular, the construction gives rise to infinite classes of supersymmetricboomerang RG flows, as well as generalising a known Janus solution.